Influence of iron additives on the corrosion resistance of the Zr-1%Nb alloy under operating conditions of a nuclear reactor - Pylypenko, M.M.; Drobyshevska, A.O.; Zuyok, V.A. (Вопросы атомной науки и техники, 2022)
This paper presents experimental data of the study of the influence of iron microadditives on the evolution of the structure of the Zr-1%Nb alloy and its corrosion properties with increasing iron content. It is shown that small additions of iron to the Zr-1%Nb alloy lead to a change in its structure due to the appearance of Laves phase precipitates. Additional micro alloying with iron makes a significant contribution to the corrosion resistance of Zr-1%Nb alloys in reactor water. The optimal amount of iron has been determined, which will lead to an increase in the corrosion resistance of the Zr-1%Nb alloy under the operating conditions of the nuclear reactor WWER-1000. Представлено експериментальні дані дослідження впливу добавок заліза на еволюцію структури сплаву Zr-1%Nb та його корозійні властивості зі збільшенням вмісту заліза. Показано, що невеликі добавки заліза до сплаву Zr-1%Nb призводять до зміни його структури через появу виділень фази Лавеса. Додаткове мікролегування сплаву залізом вносить істотний внесок в опір корозії сплавів Zr-1%Nb у реакторній воді. Визначено оптимальну кількість заліза, що призведе до підвищення корозійної стійкості сплаву Zr-1%Nb в умовах експлуатації ядерного реактора ВВЕР-1000. Представлены экспериментальные данные исследования влияния добавок железа на эволюцию структуры сплава Zr-1%Nb и его коррозионные свойства с увеличением содержания железа. Показано, что небольшие добавки железа в сплав Zr-1%Nb приводят к изменению его структуры через появление выделений фазы Лавеса. Дополнительное микролегирование сплава железом вносит существенный вклад в сопротивление коррозии сплавов Zr-1%Nb в реакторной воде. Определено оптимальное количество железа, которое приведет к повышению коррозионной стойкости сплава Zr-1%Nb в условиях эксплуатации ядерного реактора ВВЭР-1000.